Development of refrigeration simulation to enhance teaching and learning for commercial refrigeration system - Yunus, Faizal Amin Nur; Mohd Nazri, Khairul Akmal; Rahim, Mohd Bekri; Razali, Nizamuddin; Abdul Rahman, Khairul Anuar; Rozali, Zulfadli; Gerijih, Debie Devisser (Penerbit UTHM, 2021)
The lack of teaching aids in line with current needs and technology becomes a necessity in ensuring the existence of new products or innovations of existing products. Therefore the development of this product is to ease and enhance teaching and learning session of teacher and students in Commercial Refrigeration System course. The development of this product based on ADDIE model. For the functionality test, this product will test a few variable like the display of the temperature and pressure of the refrigerator in smartphone by using Blynk application to perform Mollier Chart and reading of Coefficient of Performance (CoP). Temperature and pressure were detected by sensor and connected to Arduino Wemos board that was programmed by Arduino Ide. All the information was sent to cloud and can be access the server by using smartphone. Based on result, all the functionality going well. For improvement, expert panel suggest that the display of temperature and pressure reading can be shown with easy and clearly to read. As conclusion the objectives of this product achieve to reduce high level of dependency on textbooks, enhance student’s ability to focus and improve several of teaching aids that moderate in quality.